PENGEMBANGAN KEMAMPUAN BERBAHASA ARAB BERBASIS TOAFL (TEST OF ARABIC AS A FOREIGN LANGUAGE) MELALUI PENDAMPINGAN DAN PELATIHAN DI UNIVERSITAS HASYIM ASY’ARI TEBUIRENG - Rohman, Fathur; Setyabudi, Moh. Arif; Fauzi, Mahmud (Al Tadib : Jurnal Ilmu Pendidikan, 2018)
Abstract: The article is aimed at describing the development of Arabic-based TOAFL (Testof Arabic As A Foreign Language) Arabic skills through mentoring and training. With PAR(Participatory Action Research) method, the researcher prepares the PAR stages in order toovercome difficulties and develop students' Arabic language skills. Documentation andobservation become the main techniques of data collection, and the technique of descriptiveanalysis into a way of describing the results narratively. The results of this study: First, theparticipants and the training can understand the various types or models of problemscontained in the TOAFL test; secondly, the assistant participants can understand varioustricks to answer the questions contained in the TOAFL test (Test of Arabic as a ForeignLanguage); The three assisted participants can improve the ability of the students of HasyimAsy'ari University in mastering Arabic skillsKeywords: TOAFL, Evaluation, Learning Arabic Abstrak: Artikel bermaksud membahas pengembangan kemampuan berbahasa Arabberbasis TOAFL (Test of Arabic As A Foreign Language) melalui pendampingan danpelatihan. Dengan metode PAR (Participatory Action Reseach), peneliti menyusun tahapanPAR dalam rangka mengatasi kesulitan dan mengembangkan kemampuan berbahasa Arabmahasiswa. Dokumentasi dan pengamatan menjadi teknik utama pengumpulan data, danteknik analisis deksriptif menjadi cara menggambarkan hasil secara naratif. Hasil daripenelitian ini: pertama, para peserta dampingan dan pelatihan dapat memahami berbagaimacam jenis atau model soal yang terdapat dalam tes TOAFL, kedua, Peserta dampingan dapat memahami berbagai macam trik untuk menjawab soal-soal yang terdapat dalam test TOAFL (Test of Arabic as a Foreign Language); Ketiga Peserta dampingan dapatmeningkatkan kemampuan mahasiswa Universitas Hasyim Asy’ari dalam menguasikemampuan keterampilan bahasa ArabKata Kunci: TOAFL, Evaluasi, Pembelajaran bahasa Arab